Freshwater Turtles of Belize - Venetia Briggs; Lauren Watine; Dustin Smith; Robin Bijlani; Rebecca Harvey; William Giuliano; Frank Mazzotti (EDIS)
Belize, a country rich in natural resources and diverse wildlife, is home to nine species of freshwater turtles. Among these is the critically endangered hicatee, which has been eliminated in most of its range as a result of hunting and habitat loss. Freshwater turtles live in rivers, creeks, and lagoons, and build their nests on the banks. They eat a variety of plants, aquatic vegetation, and fruits. However, little is known about Belize’s unique turtle species. This 2-page fact sheet will help people identify, understand, and conserve these treasured resources. Written by Venetia Briggs, Lauren Watine, Dustin Smith, Robin Bijlani, Rebecca Harvey, William Giuliano, and Frank Mazzotti, and published by the UF Department of Wildlife Ecology and Conservation, January 2013.